HEMATOLOGICAL AND BIOCHEMICAL PROFILES IN RHEUMATOID ARTHRITIS PATIENTS UNDERGOING METHOTREXATE, RITUXIMAB, AND COMBINATION THERAPY - Al-Shemmary, Athraa Jaleel (Journal of Medical Genetics and Clinical Biology, 2025)
Objective: Rheumatoid arthritis is one of the most prevalent chronically inflammation and systemically autoimmune illnesses. Non-steroidal anti-inflammatory medications (NSAIDs), corticosteroids, biological and synthetic disease-modifying antirheumatic pharmaceuticals (DMARDs), and immunosuppressive medications were all included in the guidelines for the treatment of rheumatoid arthritis. The aim of study Longitudinal assessment of WBC, Hb, platelets, ALT, AST, creatinine, urea, and ESR during taking Methotrexate (MTX) and Rituximab (RTX) treatment each alone and in combination for RA patients. Method: The study involved RA patient all taken treatment for 4 years divided into three subgroup: group (A) include 30 cases who were taken methotrexate only, group(B) include 20 cases were taken RTX only and group(C) include 10 cases who were taken combination of MTX and RTX for 4 year. In addition to the control group involved 60 healthy individuals. Results: Our findings reveal a significant decrease in hemoglobin (Hb) levels in RA patients undergoing these treatments (p=0.03) compared to controls(11.21,11.45, 11.21 ±SD vs. 12.56±0.96). Conversely, there was a significant increase in platelet counts (p=0.002) in treated RA patients (298.71 ,266.89,308.5±SD) compared to controls (248.96±51.54). No significant differences were observed in white blood cell (WBC) counts (p=0.26). Regarding kidney function, a significant increase in both creatinine (p=0.002) and urea (p=0.003) was noted in RA patients receiving treatment (0.69, 0.71, 0.8±SD for creatinine ; 28.5 26.88−32.34±SD for urea) when compared to controls (0.59±0.19 for creatinine; 24.63±5.51 for urea). However, liver function parameters, including ALP and AST, showed no significant differences (p=0.8 and p=0.15, respectively). Finally, a significant elevation in Erythrocyte Sedimentation Rate (ESR) (p=0.004) was observed in treated RA patients (35.63,52.81, 37.5 ±SD) versus the control group (17.7±8.47), indicating heightened inflammatory activity. Novelty: Longitudinal assessment of hematological, liver, kidney, and inflammatory biomarkers in RA patients over a four-year period under MTX, RTX, and combined treatment is rarely reported, especially with this specific comparative design including a healthy control group.